Pengaruh Job Stress Dan Career Development Terhadap Turn Over Intention Karyawan Pada PT.Garuda Food Samarinda - Muhammad ilham (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
In conjunction with human resources, changes in environmental conditions the company both internally and externally, directly or indirectly may affect career development (career development) and job stress (stress work) employees who may pose an intention to move for employees (turnover intention) which can ultimately cause the actual turnover. The purpose of this study was to determine the effect of stress on your job turnover intention of employees at PT. Garuda Food Samarinda and determine the influence of career development on employee turnover intention in PT. Garuda Food Samarinda.The results showed that job stress significant effect on turnover intention of employees at PT. Garuda Food Samarinda, job stress due to the significant value 0.007 0.05. So increasing the work stress has also increased turnover intention. Career development significant effect on turnover intention of employees at PT. Garuda Food Samarinda, career development due to the significant value of 0.002 0.05. Suggested leader or manager of PT. Garuda Food Samarinda expected to help employees cope with work stress problems, one of them to hold a counseling program. Keywords: Job Stress, Career Development, Turn Over Intention Employees